2014
DOI: 10.1007/s10658-014-0579-2
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Monilinia fructicola from Spanish peach orchards to thiophanate-methyl, iprodione, and cyproconazole: fitness analysis and competitiveness

Abstract: Benzimidazoles, dicarboximides and demethylation inhibitors are the main group of fungicides used to control brown rot in Spain. The causal agents of brown rot in peach (Prunus persica (L.) Batsch) orchards in Spain are Monilinia laxa M. fructigena, and M. fructicola. The dynamics of fungicide sensitivity and fitness of M. fructicola population, the most recent species causing brown rot in the Ebro Valley (Lleida, Spain), were characterized by determining their resistance, fitness, and in vitro competitiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 38 publications
(57 reference statements)
0
27
0
Order By: Relevance
“…Egüen et al [18] suggested that fungicide resistance of the M. fructicola population is co-acting with other factors such as an adaptation in the pathogen, changing the frequency of occurrence of the three Monilinia species in Spain. The displacement of M. laxa by M. fructicola in Spain has also been attributed to its conjugational potency related to sexual exchange and ability to produce ascopores from pseudosclerotial mummified fruits and their gradual process of a sexual propagation [56].…”
Section: Monilinia Sppmentioning
confidence: 99%
See 2 more Smart Citations
“…Egüen et al [18] suggested that fungicide resistance of the M. fructicola population is co-acting with other factors such as an adaptation in the pathogen, changing the frequency of occurrence of the three Monilinia species in Spain. The displacement of M. laxa by M. fructicola in Spain has also been attributed to its conjugational potency related to sexual exchange and ability to produce ascopores from pseudosclerotial mummified fruits and their gradual process of a sexual propagation [56].…”
Section: Monilinia Sppmentioning
confidence: 99%
“…Synthetic fungicides such as cyproconazole, iprodione, and thiophanate-methyl [18], have been used to control Monilinia in the orchards in conventional and integrated pest management programs depending of the country. As an example in the European Union, the main conventional products, allowed in Spain including application doses and maximum residue limit (MRL) for European countries is shown in Table 4.…”
Section: Fungicide Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, fungicide-based methods are not sustainable in the long term because of the emergence and subsequent spread of M. fructicola and M. laxa strains with reduced sensitivity to fungicides (Egüen et al, 2015;Ma et al, 2005;Malandrakis et al, 2013;Thomidis et al, 2009;Weger et al, 2011;. Recent studies in the Ebro Valley have detected a M. fructicola population with isolates that were single resistant, double resistant, or even triple resistant to tiophanate-methyl, iprodione and tebuconazole (Egüen et al, 2015).…”
Section: Intrinsic Host Resistancementioning
confidence: 99%
“…Recent studies in the Ebro Valley have detected a M. fructicola population with isolates that were single resistant, double resistant, or even triple resistant to tiophanate-methyl, iprodione and tebuconazole (Egüen et al, 2015). And M. laxa populations single, or double resistant to tiophanate-methyl, and iprodione (Egüen et al, 2016).…”
Section: Intrinsic Host Resistancementioning
confidence: 99%